Detection of Transcription Factor C-MYC in Oral Dysplasia and Squamous Cell Carcinoma by in Situ Hybridization - Abdul-Majeed, Ban A.; Merza, Muna S. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Oral squamous cell carcinoma continues to be a major health problem in Iraq as well as in other countries. Many attempts were made to study molecular markers in oral squamous cell carcinoma and to link them to tumor grade, stage and prognosis, besides studying their role in carcinogenesis. The present study has been designed to detect mRNA of c-myc in oral squamous cell carcinoma compared to oral dysplasia and to link the marker to grade and degree of the two pathologies. Materials and methods: Forty two cases, including 30 cases of oral squamous cell carcinoma and 12 cases of oral dysplasia were included in this study. Sections on positively charged slides were made from their paraffin blocks and were used for the detection of c-myc mRNA using in-situ hybridization technique. Results: C-myc mRNA was detected in 9(75%) cases of oral dysplasis and in 24 (80%) cases of oral squamous cell carcinoma. A significant correlation was found between c-myc mRNA score and intensity from one side and the tumor grade from the other side and degree of dysplasia. Conclusion: The results of this study confirm the role of c-myc in oral dysplasia and oral squamous cell carcinoma and the possible transfer from the former to the latter.